Pathogenetic features of pelvic floor dysfunction development in women of child-bearing age - Liliya R. Toktar; Mekan R. Orazov; Veranika E. Pak; Rustam F. Gaifullin; Lyudmila M. Mikhaleva; Konstantin Yu. Midiber; Irina A. Samsonova; Zarina N. Kamarova; Shakhlo M. Dostieva (LLC "MEDIAFORMAT", 2023)
Background. Today, the issue of genital prolapse remains in the spotlight all over the world. This condition accounts for 30-40% of all cases of gynecological diseases. It should be noted that a third of women are women of child-bearing age. The problem of understanding true prevalence of pelvic organ prolapse (РОР) in various age groups is that there are no severe clinical symptoms during early stages of the disease, which ham-pers the diagnosis and, consequently, assessment of the prevalence of genital prolapse. That is why the prevalence of genital prolapse in women of child-bearing age has been little studied in the world literature. The other feature of the РОР diagnosis in young women is that it is difficult to verify pelvic floor dysfunction (PFD) before POP manifestation. Patients often do not seek medical care, since the complaints they present with are not typical for the concept of PFD. The patients' complaints most often turn out to be related to abnormal vaginal biocenosis or even inflam-matory diseases of the pelvis, sexual dysfunctions. No treatment of such conditions results in abnormal anatomic and topographic interaction be-tween vaginal walls, reduced barrier function of introitus vaginae and altered vaginal microbiota composition, therefore, the woman suffers from recurrent pain that significantly reduces her quality of life. Aim. To study the perineal tissue state during the development of PFD. Methods. The prospective randomized comparative cohort study involved 155 women, who contacted the Department of Gynecology for elective surgical treatment. All patients underwent standard clinical and instrumental assessment for gynecological patients: history taking, physical ex-amination, advanced gynecological assessment, pelvic ultrasound. The assessment program was expanded to complex perineological examination including pelvic floor evaluation according to the method by L.R. Toktar, perineal manometry using the iEase XFT-0010 perineometer (according to the unit user manual), transperineal ultrasound. In addition, evaluation of vaginal biotope and morphological assessment of the levator com-plex were performed. Results. According to the data obtained, abnormal vaginal biotope is the major atypical PFD symptom. This condition is recurrent. The vaginal wall loss of elasticity and abnormal collagenization result in the more profound perineal tissue alterations. Morphological assessment of perineal tissues has revealed levator ani inflammation in 20% of cases and fibrosis in 100% of cases. Conclusions. Recurrent vaginal biocenosis abnormality is a clinical symptom of PFD. Vaginal dysbiosis results in morphological alterations in the vaginal wall structure and probably in the entire levator complex.